Penerapan Model Pembelajaran Examples Non Examples untuk Meningkatkan Hasil Belajar pada Siswa Kelas IV SD Kristen Selilau Kabupaten Kepulauan Aru - Soukotta, Chrisdianty Angelica; Huliselan, A.; Soplera, Marthen Luther (Universitas Pattimura, Program Studi Diluar Kampus Utama (Program Studi Pendidikan Guru Sekolah Dasar), 2022)
The research aims to know the application of the examples non examples learning model to increase the results of learning in the Christian Elmentary School in the Aru Islands Regency class IV. The purpose of this research is to increase knowledge in the development of new ideas to be used by teachers so as to improve students’ study results on the uniqueness of traditional clothing in Indonesia by applying the examples non examples learning model. In this study a type of study is used which is a reflective class action study by performing certain actions in order to improve and improve the learning practices in the classroom more professionally. As for the subject in this study, the IV class’s 11 male 9 and female 2 in the Christian Elmentary School in the Aru Islands Regency. This study, in turn, with the application of the examples non examples learning model in IPS study, will enhance the learning of superbly Christian IV-grade students